Legal Policy On Rights and Issues of Refugees in India - Rohidas Mundhe (UIN Sunan Gunung Djati, 2020)
According to the United Nations High Commissioner for Refugees in India, there are 70.8 million people who were forcibly displaced worldwide. Of these 41.3 million people displaced internally, 25.9 million were refugees, 3.9 million were stateless and 3.5 million were asylum seekers. Even if we live in the 21st century, it is a very sad situation where millions of people are deprived of their natural rights around the world. They experience various types of discrimination and torture based on race, religion, nationality, language, place of birth, membership of certain social groups or political opinion. Aiming to analyze the legal policies implemented by the Indian government for refugees, this research Â used juridical normative method with qualitative approach, literature yuridis normati and field studies, resulting in India having adopted an open door refugee policy without limiting itself to any legal framework and accommodating millions of refugees from various countries.